Competence in the handling of information through the use of ICTs - Cárdenas de Fernández, Lilia (2011)
This article presents a bibliographic review on current issues in the field of librarianship, related to skills in the management and use of information, information and communication technologies, the information and knowledge society, among others. It also aims to highlight the importance of users acquiring these skills in order to effectively face decision making, problem solving, research and their own training. This is possible if information and documentation systems participate as dynamic agents that distribute scientific and technical knowledge.